ANALISIS MANAJEMEN RESIKO PEMBIAYAAN BERMASALAH AKAD ISTISHNA DI PERUMAHAN KAMPOENG TAHFIDZ AL-KAUTSAR MUARO JAMBI (Jurnal Riset Manajemen dan Akuntansi, 2023)
This study aims to determine the financing practices of Kampoeng Tahfidz Al-Kautsar Housing in Simpang Sungei Duren Village with an al-istishna contract, to determine the factors that cause cancellation of boking and cancellation of istishna' contracts in financing Housing of Kampoeng Tahfidz al-Kautsar of Simpang Sungei Duren Village, to knowing the impact of the cancellation of the istishna' contract on the financing of Kampoeng Tahfidz al-Kautsar housing, Simpang Sungei Duren Village. This study uses qualitative research methods with primary and secondary data types. The data collection techniques used in this study were observation, interviews, and documentation. In addition to processing the data, this research was analyzed by means of data reduction, data presentation and drawing a conclusion. Based on the research results, it can be seen that housing finance in Kampoeng Tahfidz al-Kautsar does not have any criteria regarding housing buyers. But on the other hand there are some consumers who have problems in making buying and selling transactions using an istishna contract. Where out of 135 people there were 3 people who had problems financing buying and selling houses at Kampoeng Tahfidz Al-Kautsar Muaro Jambi Housing Complex. The practice of financing buyers at Kampoeng Tanfidz al-Kautsar housing is carried out in stages that have been directed by the developer to minimize the risks that will occur. These risks include credit risk, legal risk, compliance risk, strategic risk and operational risk. The cancellation of the contract also has a negative impact on consumers and sellers. Among them are the black list carried out by the Sharia Bank and Housing Kampoeng Tahfidz al-Kautsar, the loss of trust from developers or sellers to consumers who commit defaults, to losses suffered by sellers.